Factors Affecting Student Invest in The Capital Market Through the Investment Gallery of Maarif Hasyim Latif University – Sidoarjo - Adinda Rizky Maulidia; Darno Darno; Dewi Agustya Ningrum (Majalah Ilmiah Bijak, 2020)
The Indonesia Stock Exchange is intensively conducting a campaign with the theme "Let's Save Stocks" This campaign is intended to change the habits of the Indonesian people from the original savings habit now to become a habit of investing. The research aims to determine the effect of investment knowledge, investment capital, investment return, investment motivation, and investment galleries on the interest of investing in the capital market in S1 Accounting students at Maarif Hasyim Latif University - Sidoarjo.The method in this research is quantitative. The population in this study were S1 Accounting students in 2015. The samples in this study were 50 students. Data collection was carried out through a questionnaire. Instrument testing in the study used validity and reliability tests. Data analysis techniques using classical assumptions and multiple linear regression analysis.The results of the study of the influence of investment knowledge, investment capital, investment returns, investment motivation, and investment galleries on the interest of investing in the capital market on Umaha students showed that: (1) the variable of investment knowledge had no significant effect of 0.196> 0.05. (2) investment capital variable does not have a significant effect of 0.462> 0.05. (3) investment return variable has a significant effect of 0.005 <0.05. (4) investment motivation variables have a significant effect of 0.041 <0.05. (5) the investment gallery variable has no significant effect of 0.818> 0.05. (6) the independent variables jointly influence the dependent variables by 50.1%, while the remaining 49.9% are influenced by other variables not present in this study.